Fostering Customer Happiness: The Strategic Role of E-WOM, Social Media Influencers, E-Marketing, Trust, and Intention to Purchase in TikTok - Ferdy Rusyanda Ferdy; Lilik Wahyudi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study investigates the strategic roles of Electronic Word of Mouth (E-WOM), Social Media Influencers, E-Marketing, Trust, and Intention to Purchase in fostering Customer Happiness within the TikTok Live Shopping platform in Indonesia. Employing a quantitative approach, a survey was administered to 324 active TikTok Live Shopping users, and the collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that E-Marketing significantly influences Customer Happiness (T-Test = 4.9586), Intention to Purchase (T-Test = 6.1344), and Trust (T-Test = 9.8557). Interestingly, E-WOM and Social Media Influencers do not directly impact Customer Happiness. However, E-WOM significantly affects Trust (T-Test = 3.5470), while Social Media Influencers significantly influence Intention to Purchase (T-Test = 6.8632). Furthermore, Intention to Purchase is proven to positively and significantly enhance Customer Happiness (T-Test = 4.6848), and Trust emerges as a very strong predictor of Customer Happiness (T-Test = 8.3383). These findings suggest that within TikTok Live Shopping, E-Marketing, Trust, and Intention to Purchase are the primary drivers of customer happiness, with E-WOM and Social Media Influencers playing crucial roles in building trust and stimulating purchase intentions, which ultimately lead to happiness. This research contributes to digital marketing literature by providing an in-depth understanding of consumer behavior dynamics in interactive e-commerce platforms.